2016
DOI: 10.1063/1.4958514
|View full text |Cite
|
Sign up to set email alerts
|

Design a better metalloporphyrin semiconductor: A theoretical studies on the effect of substituents and central ions

Abstract: A consistent and accurate ab initio parametrization of density functional dispersion correction (DFT-D) for the 94 elements H-Puwere chosen as the central metal to see the effect of the elements on the nature of the group and the same period and reviewed the effect of substituent groups pull and push the electrons to the electronic properties of complex metalloporphyrin. The DFT/B3LYP/LANL2DZ and TD-DFT calculation were used to generate the optimized structure of, electronic and photophysical properties. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The optical band gap energy (E g ) refers to the energy difference between the HOMO and the LUMO orbitales of the porphyrin species can be calculated from the UV-visible spectrum using the Tauc plot method [42]. The E g values in CH 2 Cl 2 solution are 1.960 and 1.903 eV for [Cd(TClPP)] and [Cd(TClPP)(morph)] respectively, indicating that the gap energy of the metallized species are higher than that obtained for H 2 TClPP free base (1.820 eV)(Table S2) suggesting that the Cd-meso-porphyrin display interesting organic semiconducting properties[43].…”
mentioning
confidence: 99%
“…The optical band gap energy (E g ) refers to the energy difference between the HOMO and the LUMO orbitales of the porphyrin species can be calculated from the UV-visible spectrum using the Tauc plot method [42]. The E g values in CH 2 Cl 2 solution are 1.960 and 1.903 eV for [Cd(TClPP)] and [Cd(TClPP)(morph)] respectively, indicating that the gap energy of the metallized species are higher than that obtained for H 2 TClPP free base (1.820 eV)(Table S2) suggesting that the Cd-meso-porphyrin display interesting organic semiconducting properties[43].…”
mentioning
confidence: 99%
“…Previous study [9] showed that electron withdrawing group tend decrease the orbitals energy, but increase the gap. This effect is due to the effect of the electron density shift on the stability of the orbital is bigger on the occupied orbital than the virtual orbitals, thus decrease the orbital energy, but increase the gap between the orbitals.…”
Section: Calculation Methods Validationmentioning
confidence: 89%
“…Metalloporphyrin complexes performance as semiconducting materials is determined by the central ion of the complexes and the functional group that is substituted on the porphyrin ring [5,9]. We have previously discussed how those factors help us to design a better metalloporphyrin semiconductor by looking into the electronic structures of some meso-substituted M(II)-porphyrin (M = Pt, Cd, Hg) [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations